Preparation method and application of heavy metal ion adsorption material capable of magnetic separation
By using iron particles as the core in magnetic adsorption materials and using materials such as epoxy resin as the shell, the problems of existing materials being difficult to disperse in environmental media and oxidation and demagnetization in the adsorption material are solved, and the excellent dispersion and efficient heavy metal ion adsorption effect of the adsorption material are achieved.
Patent Information
- Application Number
- CN202310396743.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-14
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-04-14
AI Technical Summary
The existing magnetic adsorbent materials are difficult to disperse in environmental media and are prone to lose their magnetic properties due to oxidation, which affects their wide application.
The iron particles are used as the core, and the epoxy resin, aqueous epoxy curing agent and silane coupling agent are used as the adsorption materials in the shell. The iron particles are treated with dilute hydrochloric acid and concentrated nitric acid to increase their oxidation resistance, and an adsorption material with excellent dispersion properties is formed through the granulation process.
The good dispersion and oxidation resistance of the adsorbed material are achieved, the magnetic separation performance is maintained, the adsorption effect on heavy metal ions is improved, the process conditions are simplified, and industrial production is easy.
Smart Images

Figure CN116510678B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heavy metal pollution control and restoration, and in particular to a preparation method and application of a heavy metal ion adsorption material capable of magnetic separation. Background Art
[0002] Heavy metal wastewater and heavy metal pollution in soil have always been the key to environmental governance and remediation. When the content of heavy metals in environmental media exceeds a certain concentration, it will cause serious damage to the ecological environment and human health. At present, there are a variety of materials to choose from for the treatment of heavy metal wastewater and the remediation of heavy metal pollution in soil, among which magnetic adsorption materials are also one of the important options. For the remediation of heavy metal wastewater and heavy metal pollution in soil, magnetically separated adsorption materials can separate heavy metal ions from water or soil, which can solve environmental pollution problems once and for all and effectively avoid secondary pollution and other problems. In order to control the pollution of water and soil by heavy metals, seeking efficient adsorption materials has become a current research hotspot.
[0003] The traditional method for adsorbent materials that can be separated magnetically is to use ferroferric oxide with soft magnetic properties as a raw material, and to obtain functional materials that have both adsorption properties and magnetism by coating inorganic or organic materials. However, ferroferric oxide itself is prone to agglomeration, which makes it difficult to disperse adsorbent materials based on ferroferric oxide in the environmental medium. In addition, ferroferric oxide is easily oxidized in the environmental medium and loses its magnetism. This has also become the key to the widespread application of adsorbent materials that can be separated magnetically. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method of a heavy metal ion adsorbent material capable of magnetic separation and its application, so as to solve the problems existing in the prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is: a heavy metal ion adsorbing material capable of magnetic separation, wherein the heavy metal ion adsorbing material capable of magnetic separation has iron particles as a core and an organic material as an outer shell;
[0007] The organic material comprises epoxy resin, water-based epoxy curing agent and silane coupling agent.
[0008] Furthermore, the diameter of the iron particles is 100-2000 μm.
[0009] Furthermore, the epoxy resin is epoxy resin 128; the water-based epoxy curing agent is water-based epoxy curing agent WG802; and the silane coupling agent is γ-aminopropyltriethoxysilane.
[0010] The second technical solution of the present invention is a method for preparing the above-mentioned heavy metal ion adsorbent material capable of magnetic separation, comprising the following steps:
[0011] (1) pickling the iron particles with dilute hydrochloric acid and then passivating them with concentrated nitric acid to obtain passivated iron particles;
[0012] Furthermore, the mass fraction of the dilute hydrochloric acid is 5 to 20%; and the pickling time is 30 to 180 seconds.
[0013] (2) mixing epoxy resin and water-based epoxy curing agent, and adding solvent to prepare a mixture 1;
[0014] (3) placing the passivated iron particles in the mixed material 1, stirring and mixing to form the mixed material 2, and transferring the mixed material 2 to a rotary drum granulator, and granulating the mixed material 2 by the rotary drum granulator to obtain solid particles;
[0015] (4) The solid particles are mixed with water and heated, and then a silane coupling agent is added, the pH is adjusted to alkaline, and the mixture is stirred to react, thereby obtaining the heavy metal ion adsorption material capable of magnetic separation.
[0016] Furthermore, in step (1), the passivation time is 1 to 10 minutes and the temperature is 0 to 30°C.
[0017] Furthermore, in step (2), the mass fraction of the epoxy resin in the mixture 1 is 5 to 20%; the mass ratio of the epoxy resin to the water-based epoxy curing agent in the mixture 1 is (1 to 5):(1 to 10).
[0018] Furthermore, in step (3), the mass ratio of the passivated iron particles to the mixed material 1 is (1-10):10.
[0019] Furthermore, in step (4), the particle size of the solid particles is 0.1 to 2.5 mm; the heating temperature is 30 to 80° C.; the pH is 8 to 10; and the pH adjusting agent used to adjust the pH includes one or more of ammonia water, sodium hydroxide and potassium hydroxide.
[0020] Furthermore, in step (4), the mass ratio of the solid particles, water and silane coupling agent is (1-3):10:(5-10); and the stirring reaction time is 30-240 min.
[0021] The third technical solution of the present invention is to use the above-mentioned heavy metal ion adsorption material that can be separated magnetically in the treatment of heavy metal wastewater and heavy metal pollution in soil.
[0022] The present invention discloses the following technical effects:
[0023] (1) The adsorption material of the present invention has iron particles as the core and organic materials such as epoxy resin, water-based epoxy curing agent, silane coupling agent, etc. as the shell. There are multiple active groups in the shell, which can adsorb heavy metal ions.
[0024] (2) The iron particle core of the adsorption material of the present invention is passivated with concentrated nitric acid and coated with an organic material. It has good antioxidant ability and will not lose its magnetic separation performance due to oxidation of the iron particle core. In addition, the iron particle core is not easy to agglomerate, and the material has excellent dispersion properties.
[0025] (3) The synthesis process of the present invention is simple, the conditions are mild, and it is easy to operate. The required equipment is conventional equipment, which is easy to realize industrial production and has good application prospects.
[0026] (4) The adsorption material of the present invention has good adsorption performance for heavy metals, and can be quickly separated from the environmental medium (water or soil) by a magnetic field, making it easy to achieve continuous operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is a 10-fold magnified image of the heavy metal ion adsorption material capable of magnetic separation prepared in Example 1 of the present invention;
[0029] Figure 2 This is a SEM image of the heavy metal ion adsorbent material capable of magnetic separation prepared in Example 1 of the present invention;
[0030] Figure 3 This is a SEM image of the heavy metal ion adsorbent material capable of magnetic separation prepared in Example 2 of the present invention;
[0031] Figure 4 This is a SEM image of the heavy metal ion adsorbent material capable of magnetic separation prepared in Example 3 of the present invention;
[0032] Figure 5 This is a graph showing the change in the removal rate of Cd at different dosages of the heavy metal ion adsorbent material capable of magnetic separation prepared in Example 1 of the present invention;
[0033] Figure 6 This is a graph showing the change in the removal rate of Cd by the heavy metal ion adsorbent material capable of magnetic separation prepared in Example 1 of the present invention as a function of the adsorption time;
[0034] Figure 7 This is a graph showing the change in the removal rate of Cd at different dosages of the heavy metal ion adsorbent material capable of magnetic separation prepared in Example 2 of the present invention;
[0035] Figure 8 This is a graph showing the change in the removal rate of Cd at different dosages of the heavy metal ion adsorbent material capable of magnetic separation prepared in Example 3 of the present invention;
[0036] Fig. 9 This is a graph showing the change in removal rate of heavy metal cadmium in soil by the materials prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0038] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0042] Example 1
[0043] (1) Passivation of iron particles
[0044] Weigh 300g of iron particles with a particle size of 500μm, place them in 2000mL of 5% dilute hydrochloric acid for pickling for 30s, wash them with deionized water 2-3 times after pickling, and dry them at 60℃ in vacuum for 6h; then place the dried iron particles in 1000mL (8mol / L) concentrated nitric acid for passivation for 1min (the passivation temperature is 20℃), after the passivation is completed, take out the iron particles, vacuum dry them to remove the concentrated nitric acid attached to the surface of the iron particles, and then wash them with deionized water 2-3 times to remove a small amount of iron salts remaining on the surface of the iron particles, to obtain passivated iron particles;
[0045] (2) Weigh 60 g of waterborne epoxy curing agent WG802, 40 g of epoxy resin 128, and 700 g of water to prepare a mixture 1;
[0046] (3) 250 g of passivated iron particles were placed in mixed material 1, stirred and mixed for 60 min to prepare mixed material 2, and then transferred to a rotary drum granulator, and mixed material 2 was granulated by the rotary drum granulator to prepare particles with an average particle size of 1 mm;
[0047] (4) Take 20 g of the particles prepared in step (3), add 200 g of water, mix and heat to 70° C., then add 100 g of γ-aminopropyltriethoxysilane, add ammonia water to adjust the pH to 10.0, stir and react for 120 min, cool to room temperature, and perform magnetic separation with a magnet. The particles are washed with anhydrous ethanol and deionized water for 3 to 5 times, respectively, and vacuum dried at 60° C. to obtain a heavy metal ion adsorbent material that can be magnetically separated. The microscopic picture is shown in FIG. Figure 1 (magnified 10 times) and Figure 2 .
[0048] The heavy metal ion adsorption material capable of magnetic separation prepared in this embodiment has iron particles as the core and an organic material as the shell (polymer layer having heavy metal adsorption performance).
[0049] Example 2
[0050] (1) Passivation of iron particles
[0051] Weigh 100g of iron particles with a particle size of 100μm, place them in 1000mL of 5% dilute hydrochloric acid for pickling for 30s, wash them with deionized water 2-3 times after pickling, and dry them at 60℃ in vacuum for 6h; then place the dried iron particles in 1000mL (10mol / L) concentrated nitric acid for passivation for 1min (the passivation temperature is 20℃), after the passivation is completed, take out the iron particles, vacuum dry them to remove the concentrated nitric acid attached to the surface of the iron particles, and then wash them with deionized water 2-3 times to remove a small amount of iron salts remaining on the surface of the iron particles, to obtain passivated iron particles;
[0052] (2) Weigh 30 g of waterborne epoxy curing agent WG802, 20 g of epoxy resin 128, and 350 g of water to prepare a mixture 1;
[0053] (3) 100 g of passivated iron particles were placed in mixed material 1, stirred and mixed for 60 min to prepare mixed material 2, and then transferred to a rotary drum granulator, and mixed material 2 was granulated by the rotary drum granulator to prepare particles with an average particle size of 0.15 mm;
[0054] (4) Take 30 g of the particles prepared in step (3), add 100 g of water and mix, then heat to 70° C., then add 100 g of γ-aminopropyltriethoxysilane, add ammonia water to adjust the pH to 8.0, stir and react for 240 min, cool to room temperature, and perform magnetic separation with a magnet. The particles are washed with anhydrous ethanol and deionized water for 3 to 5 times, respectively, and vacuum dried at 60° C. to obtain a heavy metal ion adsorbent material that can be magnetically separated. The microscopic picture is shown in FIG. Figure 3 .
[0055] Example 3
[0056] (1) Passivation of iron particles
[0057] Weigh 100g of iron particles with a particle size of 1.5mm, place them in 1000mL of dilute hydrochloric acid with a mass fraction of 5% for pickling for 30s, wash them with deionized water 2-3 times after pickling, and dry them at 60℃ in vacuum for 6h; then place the dried iron particles in 1000mL (12mol / L) concentrated nitric acid for passivation for 1min (the passivation temperature is 20℃), after the passivation is completed, take out the iron particles, vacuum dry them to remove the concentrated nitric acid attached to the surface of the iron particles, and then wash them with deionized water 2-3 times to remove a small amount of iron salts remaining on the surface of the iron particles, to obtain passivated iron particles;
[0058] (2) Weigh 30 g of waterborne epoxy curing agent WG802, 20 g of epoxy resin 128, and 150 g of water to prepare a mixture 1;
[0059] (3) 100 g of passivated iron particles were placed in mixed material 1, stirred and mixed for 60 min to prepare mixed material 2, and then transferred to a rotary drum granulator, and mixed material 2 was granulated by the rotary drum granulator to prepare particles with an average particle size of 2.0 mm;
[0060] (4) Take 30 g of the particles prepared in step (3), add 100 g of water and mix, then heat to 70° C., then add 100 g of γ-aminopropyltriethoxysilane, add ammonia water to adjust the pH to 8.0, stir and react for 240 min, cool to room temperature, and perform magnetic separation with a magnet. The particles are washed with anhydrous ethanol and deionized water for 3 to 5 times, respectively, and vacuum dried at 60° C. to obtain a heavy metal ion adsorbent material that can be magnetically separated. The microscopic picture is shown in FIG. Figure 4 .
[0061] Comparative Example 1
[0062] 10 g of polymethyl methacrylate and 190 g of chloroform were weighed to prepare mixed material 1. 100 g of iron particles with a particle size of 0.5 mm were weighed and added to mixed material 1, and stirred and mixed for 30 minutes to prepare mixed material 2, which was then transferred to a rotary drum granulator and granulated by the rotary drum granulator to prepare particles with an average particle size of 2.0 mm.
[0063] Effect Example 1
[0064] In 150mL pH 7, Cd 2+ 0.2 g, 0.4 g, 0.6 g, 0.8 g, 1.0 g, 1.2 g, 1.4 g, and 1.6 g of the heavy metal ion adsorbent prepared in Example 1 were added to the wastewater with a concentration of 500 mg / L, respectively. The adsorption was carried out at 25 ° C with stirring (150 r / min) for 60 min. After the adsorption was completed, the Cd 2+ The removal rate was calculated and the results are shown in Figure 5 .
[0065] from Figure 5 It can be seen that at a certain concentration of Cd 2+ The greater the amount of heavy metal ion adsorbent material that can be magnetically separated is added to the wastewater, the greater the Cd 2+ The removal rate of heavy metal ions prepared in Example 1 can be separated by magnetic separation. 2 + The adsorption capacity is about 52.6 mg / g.
[0066] Effect Example 2
[0067] In 150mL pH 7, Cd 2+ 1.0 g of the heavy metal ion adsorption material capable of magnetic separation prepared in Example 1 was added to the wastewater with a concentration of 500 mg / L. The adsorption was stirred (150 r / min) for 5 min, 10 min, 20 min, 40 min, 60 min, 80 min, and 100 min at a temperature of 25 ° C. After the adsorption was completed, the Cd 2+ The removal rate was calculated and the results are shown in Figure 6 .
[0068] from Figure 6 It can be seen that at a certain concentration of Cd 2+ The heavy metal ion adsorption material that can be magnetically separated was added to the wastewater. After 60 minutes of adsorption, the adsorption basically reached equilibrium. As the adsorption time increased, Cd 2+ The removal rate did not increase significantly.
[0069] Effect Example 3
[0070] In 100mL of pH 7, Cd 2+ 0.1 g, 0.2 g, 0.3 g, 0.4 g, and 0.5 g of the heavy metal ion adsorbent material prepared in Example 2 for magnetic separation were added to the wastewater with a concentration of 500 mg / L, respectively. The adsorption was carried out at 25 ° C with stirring (150 r / min) for 60 min. After the adsorption was completed, the Cd 2+ The removal rate was calculated and the results are shown in Figure 7 .
[0071] from Figure 7 It can be seen that at a certain concentration of Cd 2+ The greater the amount of heavy metal ion adsorbent material that can be magnetically separated is added to the wastewater, the greater the Cd 2+ The removal rate of heavy metal ions prepared in Example 2 is greater than that of Cd 2 + The adsorption capacity is about 72 mg / g.
[0072] Effect Example 4
[0073] In 150mL pH 7, Cd 2+ 1 g, 2 g, 3 g, 4 g, and 5 g of the heavy metal ion adsorbent material capable of magnetic separation prepared in Example 3 were added to the wastewater with a concentration of 500 mg / L, respectively. The adsorption was carried out at 25 ° C with stirring (150 r / min) for 60 min. After the adsorption was completed, the Cd 2+ The removal rate was calculated and the results are shown in Figure 8 .
[0074] from Figure 8 It can be seen that at a certain concentration of Cd 2+ The greater the amount of heavy metal ion adsorbent material that can be magnetically separated is added to the wastewater, the greater the Cd 2+ The removal rate of heavy metal ions prepared in Example 3 can be separated by magnetic separation. 2 + The adsorption capacity is about 11.3 mg / g.
[0075] Effect Example 5
[0076] 1g, 2g, 3g, 4g, and 5g of the materials prepared in Example 1 and Comparative Example 1 were respectively placed in 100g of cadmium-contaminated soil (cadmium content was 100mg / kg), and 50g of water was added and stirred evenly. The mixture was allowed to stand for 30 days, and then the added materials were magnetically separated with a magnet. The cadmium content in the treated soil was determined, and the removal rate was calculated. The results are shown in Table 1. Fig. 9 .
[0077] from Fig. 9It can be seen that in the soil, the heavy metal ion adsorption material capable of magnetic separation prepared in Example 1 has a higher removal rate of cadmium than the material prepared in Comparative Example 1.
[0078] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A magnetically separable Cd 2+ The adsorbent material is characterized in that The magnetically separable Cd 2+ The adsorption material has iron particles as the core and organic materials as the shell; The organic material includes epoxy resin, water-based epoxy curing agent and silane coupling agent; The magnetically separable Cd 2+ The method for preparing the adsorbent material comprises the following steps: (1) passivating the iron particles with concentrated nitric acid to obtain passivated iron particles; (2) mixing epoxy resin and water-based epoxy curing agent, and adding solvent to prepare a mixture 1; (3) placing the passivated iron particles in the mixed material 1, stirring and mixing to form the mixed material 2, and transferring the mixed material 2 to a rotary drum granulator, and granulating the mixed material 2 by the rotary drum granulator to obtain solid particles; (4) adding water to the solid particles, mixing and heating, then adding a silane coupling agent, adjusting the pH to alkaline, stirring and reacting, and obtaining the Cd that can be magnetically separated. 2+ Adsorbent materials; The silane coupling agent is γ-aminopropyltriethoxysilane.
2. The magnetically separable Cd according to claim 1 2+ The adsorbent material is characterized in that The diameter of the iron particles is 100-2000 μm.
3. The magnetically separable Cd according to claim 1 2+ The adsorbent material is characterized in that The epoxy resin is epoxy resin 128; the water-based epoxy curing agent is water-based epoxy curing agent WG802.
4. The magnetically separable Cd according to claim 1 2+ The adsorbent material is characterized in that In step (1), the passivation time is 1 to 10 minutes and the temperature is 0 to 30°C.
5. The magnetically separable Cd according to claim 1 2+ The adsorbent material is characterized in that In step (2), the mass fraction of the epoxy resin in the mixture 1 is 5-20%; the mass ratio of the epoxy resin to the water-based epoxy curing agent in the mixture 1 is (1-5):(1-10).
6. The magnetically separable Cd according to claim 1 2+ The adsorbent material is characterized in that In step (3), the mass ratio of the passivated iron particles to the mixed material 1 is (1-10):
10.
7. The magnetically separable Cd according to claim 1 2+ The adsorbent material is characterized in that In step (4), the particle size of the solid particles is 0.1 to 2.5 mm; the heating temperature is 30 to 80° C.; the pH is 8 to 10; and the pH adjusting agent used to adjust the pH includes one or more of ammonia water, sodium hydroxide and potassium hydroxide.
8. The magnetically separable Cd according to claim 1 2+ The adsorbent material is characterized in that In step (4), the mass ratio of the solid particles, water and silane coupling agent is (1-3):10:(5-10); and the stirring reaction time is 30-240 min.
9. A magnetically separable Cd according to any one of claims 1 to 8 2+ Adsorption materials are used in the treatment of heavy metal wastewater and heavy metal pollution in soil.
Citation Information
Patent Citations
Preparation method of thiol-functionalized magnetic silica nano-material
CN103599751A
Preparation process of soft magnetic composite material stator
CN114513099A